2022
DOI: 10.1038/s41598-022-06002-3
|View full text |Cite
|
Sign up to set email alerts
|

Human ignitions on private lands drive USFS cross-boundary wildfire transmission and community impacts in the western US

Abstract: Wildfires in the western United States (US) are increasingly expensive, destructive, and deadly. Reducing wildfire losses is particularly challenging when fires frequently start on one land tenure and damage natural or developed assets on other ownerships. Managing wildfire risk in multijurisdictional landscapes has recently become a centerpiece of wildfire strategic planning, legislation, and risk research. However, important empirical knowledge gaps remain regarding cross-boundary fire activity in the wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Moreover, the population increase signifies the expansion of private land, raising concerns as private land fragmentation interferes with public land and undermines mitigation efforts. Given that most wildfires initiate on private land (Downing et al 2022), the prevalence of human-induced fires, combined with personal property serving as a wildfire starting point, underscores population change as a significant factor contributing to heightened wildfire risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the population increase signifies the expansion of private land, raising concerns as private land fragmentation interferes with public land and undermines mitigation efforts. Given that most wildfires initiate on private land (Downing et al 2022), the prevalence of human-induced fires, combined with personal property serving as a wildfire starting point, underscores population change as a significant factor contributing to heightened wildfire risk.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has prompted insurance companies to deny coverage to residents in high wildfire-risk zones throughout California (Kramer et al 2019, Gonzalez 2023. The substantial proportion of wildfires originating from private land within the WUI intensifies the exposure of properties to risk (Downing et al 2022). Additionally, the density of structures in interface communities, coupled with inadequate response time such as fire-fighting compliant road access, poses challenges for preventing loss of buildings (Glickman and Babbit 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Wildland fires in the United States are becoming more intense and more frequent in the 21st century (Dennison et al, 2014; Senande‐Rivera et al, 2022). Fires on public lands result in economic and recreational damage and can impact surrounding communities if the spread of the fire is not contained (Bawa, 2017; Downing et al, 2022). Also, fires can be ignited on private lands and cross boundaries into public land, causing widespread impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies examined only a single fire event, with very little work done at larger geographic scales on cross‐boundary risk associated with ownership type or management approach (but see Downing et al . 2022). Here, our goal was to quantify the impact of land ownership on the incidence of high‐severity fire, conditional on fire occurrence, through large‐scale analyses of wildfires in California.…”
mentioning
confidence: 99%
“…Several have demonstrated reduced fire severity and area burned in industrially managed forests (Lyons-Tinsley and Peterson 2012; Starrs et al 2018), whereas others have reported increased severity (Zald and Dunn 2018). Most of these studies examined only a single fire event, with very little work done at larger geographic scales on crossboundary risk associated with ownership type or management approach (but see Downing et al 2022). Here, our goal was to quantify the impact of land ownership on the incidence of high-severity fire, conditional on fire occurrence, through large-scale analyses of wildfires in California.…”
mentioning
confidence: 99%